An evaluation of current diagnostic tests for the detection of infectious salmon anaemia virus (ISAV) following experimental water‐borne infection of Atlantic salmon, Salmo salar L. - M Snow; R S Raynard; A G Murray; D W Bruno; J A King; R Grant; I R Bricknell; N Bain; A Gregory (Journal of Fish Diseases, 2003)
Four commonly used diagnostic tests [reverse transcription polymerase chain reaction (RT‐PCR), indirect fluorescent antibody test (IFAT), virus culture and light microscopy] were evaluated for their ability to detect infectious salmon anaemia virus (ISAV) or tissue pathology following experimental infection of Atlantic salmon. Fish were infected with ISAV by water‐borne exposure which mimics the route of natural infection. Forty‐five per cent of pre‐clinical fish tested yielded positive results by RT‐PCR for at least one of the organs tested (kidney, heart, gill, liver, blood). No significant difference was detected between organs in the number or time of first occurrence of positive result. Virus culture identified a total of 14% of pre‐clinical fish as ISAV‐infected. The presence of ISAV in heart tissue was particularly notable (13% of fish sampled) as was the inability to culture virus from spleen tissue. In the case of IFAT, 15% of fish sampled were positive, although tissue other than kidney proved unsuitable for use in this method. Only limited ISAV‐specific pathology was detectable by histological examination of fish prior to the onset of clinical disease. These findings reveal important information regarding the optimal choice of both tissue sample and diagnostic test for the routine diagnosis of ISAV.